Proprotein convertase subtilisin/Kexin type-9 (PCSK-9) inhibitors induced liver injury - a retrospective analysis. Issue 1 (2nd January 2020) - Zafar, Yousuf; Sattar, Yasar; Ullah, Waqas; Roomi, Sohaib; Rashid, Mamoon-Ur-; Khan, Muhammad Shayan; Schmidt, Laura
ABSTRACT: Background: Proprotein convertase subtilisin/Kexin type 9 (PCSK-9) inhibitors induced liver dysfunction in patients with or without previous liver injury, and this is not well discussed in the previous literature. Methods: A total sample of 202 patients were retrospectively reviewed at the University of Missouri, Kansas City, from the year 2015 to 2018 based on predefined selection criteria. Inclusion criteria involved patients with dyslipidemia, with or without PCSK-9 inhibitors, liver function tests and lipid profile at baseline and at a mean of 6-month follow-up. The variables, including age, gender, and confounding factors like other medications (statin, oral antidiabetic, and antihypertensive) induced, or chronic secondary liver diseases causing liver injury were taken into consideration. Exclusion criteria included patients without dyslipidemia. Results: The mean age of the study population was 64 ± 11 years (63% males and 37% females). The lipid profile including triglyceride and cholesterol levels during 6-month follow-up visit showed a mean of 184 ± 260 and 163 ± 50 mg/dL as compared to that at baseline of 227 ± 603 and 181 ± 70 mg/dL, respectively. In terms of clinical efficacy, a 6-month follows-up showed a drop in triglyceride and cholesterol levels by 38 and 15 mg/dL, respectively. A liver function test at 6 months in patients taking PCSK-9 inhibitors showed an increase in alanine transaminase (ALT) and aspartate transaminase (AST) by 5.8 mg/dL ( p = 0.037) and 6.2 mg/dL ( p = 0.008), respectively, from baseline values. Conclusion: PCSK-9 inhibitors should be used cautiously with a follow-up liver function test.